Teachers and Students’ Perception Toward English Authentic Reading Materials Used in Junior High School - Ilahi, Lailiy Kurnia; S, Maghfiroh Agustinasari S; Taufik, Moh.; Wicaksana, Roziyan Adi (UNIB Press, 2024)
The research was conducted to find the perceptions of English teachers and students toward the use of authentic reading materials in schools. The study was conducted at three junior high schools in Pamekasan. A research survey was employed with seven steps: (1) Questionnaire Development and Validation; (2) Try-Out; (3) Questionnaire Distribution; (4) Data Analysis; (5) Interview; (6) Result; and (7) Conclusion. In collecting the data, two kinds of instruments, consisting of a close-ended questionnaire, were distributed via Google form to six English teachers and 73 students in grade nine, and an interview with the English teachers was conducted. Using SPSS for data analysis, the results showed that 83.3% of teachers strongly agreed that authentic materials are up-to-date and relevant to everyday life, with an average score of 3.8 on a 4-point Likert scale. For students, 75.3% agreed that authentic materials increased their interest in reading English texts, with an average score of 3.1. The research findings revealed that authentic reading materials in the ninth grade had various advantages; the material taught is easy to understand, up-to-date, relevant to everyday life, increases the students’ motivation, and mastering vocabulary. Meanwhile, there were various disadvantages; students still feel sluggish when they must read the assigned text; they require more time to grasp the text; it is difficult to locate appropriate authentic material for students; and students hope that teacher will leave the class soon. In conclusion, while authentic reading materials present certain challenges, their benefits in enhancing student engagement and motivation outweigh the drawbacks. Teachers can address these challenges by implementing a variety of solutions to improve the teaching and learning process.